2001
DOI: 10.1016/s0006-3495(01)75802-x
|View full text |Cite
|
Sign up to set email alerts
|

Barrel-Stave Model or Toroidal Model? A Case Study on Melittin Pores

Abstract: Transmembrane pores induced by amphiphilic peptides, including melittin, are often modeled with the barrel-stave model after the alamethicin pore. We examine this assumption on melittin by using two methods, oriented circular dichroism (OCD) for detecting the orientation of melittin helix and neutron scattering for detecting transmembrane pores. OCD spectra of melittin were systematically measured. Melittin can orient either perpendicularly or parallel to a lipid bilayer, depending on the physical condition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
956
1
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 977 publications
(1,016 citation statements)
references
References 65 publications
45
956
1
14
Order By: Relevance
“…Both gave the same results in this study. Yang et al (35) also found no difference between Sigma melittin and pure synthetic melittin in this type of study as long as there was no added Ca 2+ in the sample. Poly(ethylene glycol) (PEG20000) was purchased from Merk Co. (Hohenfrunn, Germany).…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…Both gave the same results in this study. Yang et al (35) also found no difference between Sigma melittin and pure synthetic melittin in this type of study as long as there was no added Ca 2+ in the sample. Poly(ethylene glycol) (PEG20000) was purchased from Merk Co. (Hohenfrunn, Germany).…”
Section: Methodsmentioning
confidence: 49%
“…Melittin, magainin, protegrin, and perhaps most cationic antimicrobial peptides form toroidal pores (35). In this paper, alamethicin and melittin are used to study these two types of pores.…”
mentioning
confidence: 99%
“…Melittin forms an amphipathic a-helix in aqueous solution and interacts with lipid membranes through a positively charged cluster (KRKR). The mechanism by which melittin inserts into the membrane and disrupts it has been vigorously studied, and evidence supports a model in which it forms toroidal pores 129,130 (Figure 3a). In this model, the peptides induce perturbations in the membrane and bend it so that the top and bottom layers of the bilayer join contiguously at the pore wall.…”
Section: Endosomolysismentioning
confidence: 81%
“…The antimicrobial peptides studied are known to adopt an R-helical structure in the presence of membranes. 15,21,23,25,60 The importance of this structure for antimicrobial activity has been a subject of debate, whereas the influence of membrane charge on peptide-membrane interaction is relevant for the development of selective antibiotics. 5,20,30,49,61 From the present work, we can conclude that DSC provided a detailed insight intosand differentiation betweensthe interactions of two cecropin A-melittin hybrid peptides with three lipid model systems.…”
Section: Discussionmentioning
confidence: 99%
“…16 Other investigations on microorganisms confirmed that, generally, antimicrobial peptides exert their activity by permeabilizing the plasma membrane. 3,11,17,18 Alternative mechanisms of action have been proposed for some antimicrobial peptides, 4,[19][20][21][22][23][24][25][26][27][28] and the requirements for peptide antimicrobial activity have also been extensively discussed. 3,[29][30][31][32][33] Differential scanning calorimetry (DSC) has emerged as a most valuable tool to study peptide-membrane interactions.…”
Section: Introductionmentioning
confidence: 99%